ANALYSIS OF THE INFLUENCE OF TAX PLANNING AS AN EFFORTS TO MINIMIZE TAX LOADS ON COMPANY VALUE WITH TRANSPARENCY OF COMPANIES AS MODERATING VARIABLES (CASE STUDY IN COMPANIES INCLUDING LQ45 IN THE 2012-2015 INDONESIA EXCHANGE) - Hisam Mubarak; Asep Kurniawan; Asri Suangga (STIESA Press, 2019)
This study aims to analyze the effect of tax planning on company value with transparency as a moderating variable. The population of this study are all companies included in LQ45 on the Indonesia Stock Exchange in 2012-2014 who reported complete and published finances. The sample selection technique uses purposive sampling. Samples that fit the criteria are 22 companies. Testing in this study uses a simple linear regression test and Moderated Regression Analysis (MRA) which includes the classic assumption test, the coefficient of determination (R2), t test, and F test and to analyze data using SPSS Version 22. The results of this study indicate that tax planning affects the value of the company with a negative direction, which means that every time there is an increase in tax planning, the value of the company will go down. Then transparency is able to moderate the relationship between tax planning on company value, its influence strengthens showing that transparency can reduce the negative effects of tax planning so that the company's value rises.